2016
DOI: 10.1002/pits.21971
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐teacher Relationships in Elementary School: An Examination of Parent‐teacher Trust

Abstract: Trust is an important dimension of parent educational involvement and parent-teacher relationships. Preliminary research suggests that parent trust in teachers and schools is associated with student learning and behavior. However, examinations of parent trust in children's education are limited. The present study investigated the influence of demographic variables on parent trust and relations among parent trust, student behavior, and parent involvement. Findings suggested that student eligibility for a free o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 39 publications
2
53
0
Order By: Relevance
“…In fact, it has been recommended that school staff reach-out to families to lay the foundation of open and trusting family-school relationships that serve as the basis for academic and behavior supports for children (Christenson & Reschly, 2009). In turn, these open and trusting relationships can influence family involvement (Santiago et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been recommended that school staff reach-out to families to lay the foundation of open and trusting family-school relationships that serve as the basis for academic and behavior supports for children (Christenson & Reschly, 2009). In turn, these open and trusting relationships can influence family involvement (Santiago et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…There are many components to consider for successful family-school partnerships, including the quality and quantity of communication between parents and teachers. Studies in general education have shown that improving the quality of home-school communication, not just the frequency of contact, is a primary way to enhance trust in the parent-teacher relationship and further promote parental involvement (Santiago, Garbacz, Beattie, & Moore, 2016). More specifically, parents of typically developing children want teachers to provide specific information on their child’s academic content and learning goals, as well as clear direction on how to incorporate learning opportunities at home (Christenson, 2004; Epstein & Dauber, 1991).…”
mentioning
confidence: 99%
“…As introduced, parental self-efficacy expectation predicts student achievement in German. Therefore, and in line with prior research, it is assumed that parents' trust affects student achievement (Adams & Christenson, 2000;Santiago, Garbacz, Beattie, & Moore, 2016). This effect is mediated by parent self-efficacy expectation in German, but not in mathematics.…”
Section: Parent-teacher Cooperation and Student Achievementmentioning
confidence: 75%
“…Parents in trusting relationships with teachers send verbal and nonverbal signals to children that learning and schooling are important (Adams & Christenson, 2000). These attainment values are internalized by the child (Eccles & Wigfield, 2002) and motivate the child to learn, which results in higher achievement (Adams & Christenson, 2000;Santiago et al, 2016). Moreover, parents and teachers who experience a trusting relationship better coordinate student-related activities and feedback.…”
Section: Discussionmentioning
confidence: 99%